A Low‐Temperature Batch Process for the Deposition of High‐Quality Conformal Alumina Thin Films for Electronic Applications - Gregory Burwell (Advanced Engineering Materials, 2023)
High-quality, alumina thin films are extensively used as dielectrics, passivation layers and barrier layers in electronics and many other applications. However, to achieve optimum stoichiometry and thus performance, the layers are often grown at elevated temperatures (> 200 °C) using techniques such as Atomic Layer Deposition (ALD). This is problematic for substrates or structures with low thermal budgets. In this work, alumina thin films were grown on 200 mm silicon substrates employing a versatile deposition method known as Molecular Vapour Deposition (MVD) at low deposition temperatures (35-150 °C). The chemical composition of the resulting films was investigated post-deposition using X-ray Photoelectron Spectroscopy (XPS) and Variable Angle Spectroscopic Ellipsometry (VASE), with fully stoichiometric Al2O3 achieved at deposition temperatures as low as 100 °C. Dielectric measurements confirm outstanding dielectric properties compared to typical thermal ALD layers deposited at much higher temperatures. We rationalise and understand this low-temperature deposition performance by considering the MVD reactor design and the ‘pump-type’ regime of precursor delivery versus the ‘flow-type’ regime of ALD. Our results clearly demonstrate that alumina thin films grown with MVD are highly versatile for electronic applications and are of particular relevance and interest for the high-volume processing of dielectric, passivation, and barrier layers at low temperatures.